2012
DOI: 10.1021/nl203965w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Scale Conductance Photoswitching in Engineered Bacteriorhodopsin

Abstract: Bacteriorhodopsin (BR) is a robust light-driven proton pump embedded in the purple membrane of the extremophilic archae Halobacterium salinarium. Its photoactivity remains in the dry state, making BR of significant interest for nanotechnological use. Here, in a novel configuration, BR was depleted from most of its endogenous lipids and covalently and asymmetrically anchored onto a gold electrode through a strategically located and highly responsive cysteine mutation; BR has no indigenous cysteines. Chemisorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
(73 reference statements)
3
29
0
Order By: Relevance
“…In addition to enhancing the lifetime of different photocycle intermediates of BR, mutagenesis has been employed to enhance the innate dipole moment, gold-binding capabilities and specificity of ion pumping of BR. For a number of device platforms and architectures, the ability of BR to bind to gold is critical because gold is a chemically inert and electrically conductive [112][113][114]. The native protein contains no cysteine residues and thus the strategic addition of cysteine residues in the loop regions of BR via site-directed mutagenesis allows BR to rsif.royalsocietypublishing.org J R Soc Interface 10: 20130197 covalently bind to gold.…”
Section: Optimization Strategiesmentioning
confidence: 99%
“…In addition to enhancing the lifetime of different photocycle intermediates of BR, mutagenesis has been employed to enhance the innate dipole moment, gold-binding capabilities and specificity of ion pumping of BR. For a number of device platforms and architectures, the ability of BR to bind to gold is critical because gold is a chemically inert and electrically conductive [112][113][114]. The native protein contains no cysteine residues and thus the strategic addition of cysteine residues in the loop regions of BR via site-directed mutagenesis allows BR to rsif.royalsocietypublishing.org J R Soc Interface 10: 20130197 covalently bind to gold.…”
Section: Optimization Strategiesmentioning
confidence: 99%
“…Electron conduction through these purple membranes was measured recently (9) in ambient and as a function of temperature (10). Electrochemical and conduction studies were also performed when the purple membranes were deposited on gold (11).…”
mentioning
confidence: 99%
“…Specifically, purple membrane, which contains a mutant of bacteriorhodopsin (bR), can serve as a light‐activated spin switch. This system has been previously suggested as a candidate for bio‐electronics, and in a former study, wild‐type bR was shown to have spin‐filtering properties . Spin‐dependent electrochemical studies were conducted on purple membrane containing a mutant of bacteriorhodopsin (bR) adsorbed on nickel substrates .…”
Section: The Ciss Effectmentioning
confidence: 90%
“…An interesting aspect of usingC ISS for spintronics is applying biosystemsa sac omponent in electronic devices like spin valves.B ecause of its stable structure and ease of combining with inorganic interfaces, the use of bacteriorhodopsin (bR)w as investigated in detail among other combinations,b ecause of the possibility to use bR for controlling spintronics with light. [14] Specifically,p urple membrane,w hich contains am utant of bacteriorhodopsin (bR), can servea salight-activateds pin switch.T his system has been previously suggested as ac andidate for bio-electronics [15,16] and in af ormers tudy,w ild-type bR was shown to have spin-filtering properties. [17] Spin-dependent electrochemicals tudies were conducted on purple membrane containingamutant of bacteriorhodopsin (bR) adsorbed on nickel substrates.…”
Section: Spintronicswith Bio-systemsmentioning
confidence: 99%